Air Pollution and Internal Migration: Evidence from Iranian Household Survey - Hassan F. Gholipour; Mohammad Reza Farzanegan; Mostafa Javadian (Center for Economic Studies and ifo Institute (CESifo), 2020)
The purpose of this study is to examine the impact of air pollution (measured by satellite data of Aerosol Optical Depth (AOD)) on net outmigration. Using data from the 2011 and 2016 National Population and Housing Censuses for 31 provinces of Iran and applying a panel fixed effects estimation method, our results show that AOD has a positive and significant impact on net outmigration. We also find that higher levels of economic activities in provinces discourage outmigration.
Keywords: Q53; R23; 330; air pollution; migration; Iran